A conceptual framework for understanding and developing entrepreneurial behaviour: implications for social marketers. Issue 4 (29th June 2015) - Jebarajakirthy, Charles; Thaichon, Paramaporn
<x xml:space="preserve">Abstract</x> Inculcating entrepreneurial behaviour is beneficial to both individuals and the society at large. The Theory of Planned Behaviour has been generally applied to understand and examine entrepreneurial behaviour. However, as the underpinnings of this theory are not adequate for understanding the entire process of the development of entrepreneurial behaviour, a more comprehensive theoretical framework is required. Combining the Theory of Planned Behaviour with the Stages of Change Theory provides such a comprehensive theoretical framework. The Stages of Change Theory is used in the social marketing field to facilitate behavioural change, which has also been recently applied in organizational‐related studies, such as change management. A methodological and analytical approach is also suggested for empirically validating the framework developed in this study. The implications of this framework for theory and practice are discussed, as are directions for future research, which would be of use to researchers and practitioners in the social marketing field. Copyright © 2015 John Wiley & Sons, Ltd.